Convergence of deep learning and internet of things computing and technology - Kavitha, T. 1979-; Senbagavalli, G.; Koundal, Deepika; Guo, Yanhui; Jain, Deepak (Advances in computational intelligence and robotics (ACIR) book series, 2023)
For those interested in design and building intelligent Internet of Things, this research book offers solutions with the state-of-the-art and novel approaches for the IoT problems and challenges from a deep learning perspective.